PENGARUH SYIAH DALAM KEHIDUPAN MASYARAKAT ACEH (Refleksi atas Naskah Hikayat Hasan Husain dan Nu>r Muh}ammad) - Fakhriati, Fakhriati (Analisis: Jurnal Studi Keislaman, 2011)
Abstract The  article  examines  the  traces  of ideology  and  practices  of Shia teachings that developed in Indonesia, particularly Aceh by analyzing two  popular  texts  in Acehnese  society,  especially  the  Pidie region, the story of Hasan and Husain and Nu r Muhammad. To this end, the author uses an interdisciplinary approaches; first it uses philology and codicology to assess the content and the physic of the manuscript. Then the inter-textual approach is used to compare the text of the manuscript with similar texts in order to obtain information related to the cultural practices of the Shia in Acehnese society. Then to analyze the context of the background  and the existence  of the manuscript  appeared in the local community even its popularity it uses the approach of social history. The authors found that the two texts being studied describe that people were really appreciated  and reflected history of the past, then they use it as a spirit in their lives. Persistent  struggle and relentless fight the people of Aceh against in disbelief and colonialism, perhaps, was part of a reflection of genuine appreciation  for the history of the struggle  of ‘Ali and his family that  they  were praised in the  saga.